Rancang Bangun Sistem Pengundian Sepakbola Menggunakan Logika Fuzzy - Irving Vitra Paputungan; Denni Irawan (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2005)
There are alot of change in football since last century. Football become a great stuff in humans life,especially in Europe. Inspired by Champions League and World Cup, there are several clubs that become agreat clubs with their players, landmarks, and history.This paper will try to create an application that can draw some clubs(32) in a turnament with fuzzy logic.The draw will use Tsukamoto Methods.Keywords: football, drawing, fuzzy logic.